2021
DOI: 10.1590/1414-431x20209764
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin promotes cell autophagy to improve high-fat-diet-induced atherosclerosis in ApoE-/- mice

Abstract: Naringenin (NAR) is a major flavanone in citrus fruits that has multiple pharmacological attributes such as anticancer and antiatherogenic. This study aims to investigate the mechanism of NAR in high-fat-diet (HFD)-induced atherosclerosis (AS) in apolipoprotein E-knockout (ApoE-/-) mice. A HFD-induced AS ApoE-/mouse model was established. The mice were treated with HFD, different doses of NAR and simvastatin (Simv). After drug treatment, the levels of total cholesterol (TC), triglyceride (TG), low density lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 38 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Moreover, CA attenuates the aorta lesion region in rats fed with atherosclerogenic diet compared with those fed with normal diet 36 . Zhao et al showed that naringenin reduces the atherosclerotic plaque area through the promotion of autophagy in ApoE-/- mice fed with high fat diet 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CA attenuates the aorta lesion region in rats fed with atherosclerogenic diet compared with those fed with normal diet 36 . Zhao et al showed that naringenin reduces the atherosclerotic plaque area through the promotion of autophagy in ApoE-/- mice fed with high fat diet 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that naringenin induces autophagy in neural cells and mice [44,45]. This prompted us to examine whether mechanisms associated with autophagy were altered in lung cancer cells in response to naringenin.…”
Section: Naringenin Promoted Autophagy Through Ros-induced Activation...mentioning
confidence: 98%